TRPV1 in dorsal root ganglion contributed to bone cancer pain - Chen, Wen; Li, Hongping; Hao, Xiaowan; Liu, Cunzhi (Frontiers in Pain Research, 2022)
Tumor growth in situ or bone metastases in cancer patients all can induce bone cancer pain. It is frequently occurred in patients with breast, prostate, and lung cancer. Because of the lack of effective treatment, bone cancer pain causes depression, anxiety, fatigue, and sleep disturbances in cancer patients, disrupts the daily quality of life, and results in huge economic and psychological burden. Over the past years, transient receptor potential channels (TRPs), especially TRP vanilloid 1 (TRPV1) in dorsal root ganglion (DRG), have been considered to be involved in bone cancer pain. The characteristic of TRPV1 had been well studied. The mechanisms under TRPV1 regulation in DRG with bone cancer pain are complex, including inflammatory mediators, endogenous formaldehyde, and other mechanisms. In the present review, we summarize the role and potential mechanism of TRPV1 in DRG in bone cancer pain. As the primary sensory neurons, targeting the TRPV1 channel in DRG, might have fewer side effects than in central. We hope systematically understand of TRPV1 modulation in DRG will bring more effective strategy.